1993
DOI: 10.1001/archpsyc.1993.01820230066006
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Rank Attainment and Research Activities Among Academic Psychiatrists

Abstract: Data from a survey distributed to all full-time faculty in academic departments of psychiatry were used to examine possible sex differences in research activities and rank attainment among psychiatrists. A total of 1923 psychiatrists responded, 1564 men (81.3%) and 359 women (18.7%). Continuous dependent variables were analyzed by using analyses of covariance with the year graduated from medical school as a covariate. For categorical dependent variables, the sample was divided into four 10-year cohorts based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Efforts to increase recruitment into research should centre on identifying early developmental influences, eliminating barriers specific to women or minorities (Goldstein et al, 2014), and ensuring adequate funding to provide secure careers for talented potential researchers (Silberman et al, 2012). Although research has not identified specific gender inequalities in research activities, these issues need to be addressed in future research (e.g., (Leibenluft et al, 1993)), as the number of women and minorities in research remain low (Abrams et al, 2003).…”
Section: Fundingmentioning
confidence: 99%
“…Efforts to increase recruitment into research should centre on identifying early developmental influences, eliminating barriers specific to women or minorities (Goldstein et al, 2014), and ensuring adequate funding to provide secure careers for talented potential researchers (Silberman et al, 2012). Although research has not identified specific gender inequalities in research activities, these issues need to be addressed in future research (e.g., (Leibenluft et al, 1993)), as the number of women and minorities in research remain low (Abrams et al, 2003).…”
Section: Fundingmentioning
confidence: 99%
“…Tait & Platt (1995) found female consultants were less likely to receive merit awards. Women are underrepresented in medical school faculties (Heslop, 1987) and tend to achieve lower ranks if they pursue academic careers (Leibenluft et al, 1993). Stratton et al (2005) found that although large proportions of medical students had observed or experienced gender discrimination or sexual harassment, females were significantly more likely to describe such experiences as affecting their choice of specialty.…”
Section: Do Women Choose Psychiatry Because It Fits In Better With Famentioning
confidence: 99%
“…Productivity within the academy is consistent with productivity without. Studies of scholarly output regularly show that men, on average, publish substantially more than women, whether or not the women have children (Persell, 1983;Cole and Zuckerman, 1987;Long, 1992;Leibenluft et al, 1993;Primack and Stacy, 1997).…”
Section: Women's Wagesmentioning
confidence: 99%